Evaluating the effect of cultivation conditions on palmitoleic acid‐rich lipid production by Scheffersomyces segobiensis DSM 27193. (16th September 2021) - Zhou, Xinhai; Bao, Xinhui; Zhou, Jie; Xin, Fengxue; Zhang, Wenming; Qian, Xiujuan; Dong, Weiliang; Jiang, Min; Ochsenreither, Katrin
Abstract: Palmitoleic acid (POA) is a valuable monounsaturated fatty acid but it is rarely found in high proportions in microbial lipids. Recently, the newly isolated oleaginous yeast Scheffersomyces segobiensis DSM 27193 has been confirmed to be able to accumulate >10% POA in its intracellular lipids. This study comprehensively investigated the effect of medium composition and cultivation conditions on POA‐rich lipid accumulation by this yeast. The results showed that the lipid content could be improved significantly in shake flask cultivations from 3.6% to 27.3% by using yeast extract as a nitrogen source. Increasing Mg 2+ concentration from 0.04 to 0.16 g L −1 resulted in the formation of 15.3 g L −1 of biomass and 4.2 g L −1 of POA‐rich lipids. The initial pH, temperature, and inoculation size also influenced POA‐rich lipid production positively. Under optimal conditions, the highest lipid content of 31.7% with the highest POA content of 12.50% was achieved, corresponding to 5.3 g L −1 of lipids and 0.7 g L −1 of POA. Fermentation conducted in a 2.5 L bioreactor led to 28.1 g L −1 of biomass with 39.4% of lipid content, corresponding to 11.1 g L −1 of total lipids and 1.4 g L −1 of POA. These results suggest that this yeast could be a potentially well‐suited host for POA‐rich lipid production. © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd